2022
DOI: 10.3390/su14159600
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Assessment Method for Simply Supported Bridge Based on Structural Health Monitoring of Frequency with Temperature and Humidity Effect Eliminated

Abstract: Structural health monitoring (SHM) has been widely used for the performance assessment of bridges, especially the methods based on dynamic characteristics. Meanwhile, bridge modal frequency is influenced significantly by environmental factors, such as temperature and humidity. Combined with SHM, a reliability assessment of bridges with the temperature and humidity effects eliminated is proposed. Firstly, the bridge deflection verification coefficient is adopted as the evaluation indicator for bridge condition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The proposed technique can eliminate the effects of humidity and temperature on structural responses. He et al [195] proposed a reliability assessment approach for bridge structures. This method is capable of eliminating temperature and humidity effects.…”
Section: Humiditymentioning
confidence: 99%
“…The proposed technique can eliminate the effects of humidity and temperature on structural responses. He et al [195] proposed a reliability assessment approach for bridge structures. This method is capable of eliminating temperature and humidity effects.…”
Section: Humiditymentioning
confidence: 99%
“…Thus, early damage detection of bridges has become an important and indispensable part of structural health monitoring (SHM) systems for high-speed railways, and the application of new methods or new materials in the field of SHM has been widely studied [3][4][5][6][7][8]. Extensive research efforts have been devoted to damage detection, and many effective methods have been proposed [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Their research indicated that an increase in temperature leads to a decrease in modal frequencies and damping ratios, while modal frequencies and damping ratios show no significant correlation with humidity. He et al [23] considered the influence of temperature and humidity on frequency monitoring data and developed a temperature and humidity elimination method based on BP neural networks, improving the accuracy of bridge condition reliability assessment. He et al [24] established a "Frequency-Temperature-Humidity" long-term equilibrium model based on cointegration theory for monitoring data from a three-span concrete bridge model.…”
Section: Introductionmentioning
confidence: 99%